Patient suspected susceptibility to malignant hyperthermia: impact of the disease - Rodrigues, Gislene [UNIFESP] (2023)
Introduction Malignant Hyperthermia (MH) is an inherited hypermetabolic syndrome triggered by exposure to halogenated anesthetics/succinylcholine. The lack of knowledge regarding this condition might be associated with the rare occurrence of MH reaction and symptoms. Methods This observational study evaluated 68 patients from 48 families with confirmed or suspected MH susceptibility due to medical history of MH reaction or idiopathic increase of creatine kinase or MH-related myopathies. Participants were assessed by a standardized questionnaire and submitted to physical/neurological examination to assess the characteristics of patients with MH, their knowledge about the disease, and the impact suspected MH had on their daily lives. Results Suspected MH impacted the daily life of 50% of patients, creating difficulties in performing surgical/clinical/dental treatment and problems related to their family life/working/practicing sports. The questionnaire on MH revealed a correct answer score of 62.1 ± 20.8 (mean ± standard deviation) on a scale 0 to 100. Abnormal physical/neurological examination findings were detected in 92.6% of susceptible patients. Conclusions Suspected MH had impacted the daily lives of most patients, with patients reporting problems even before MH investigation with IVCT. Patients showed a moderate level of knowledge about MH, suggesting the need to implement continuing education programs. MH susceptible patients require regular follow-up by a health team to detect abnormalities during physical and neurological examination.